2021
DOI: 10.3390/coatings11050557
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Protective Coatings for Accident Tolerant Zr-Based Fuel Claddings

Abstract: Zirconium-based alloys have served the nuclear industry for several decades due to their acceptable properties for nuclear cores of light water reactors (LWRs). However, severe accidents in LWRs have directed research and development of accident tolerant fuel (ATF) concepts that aim to improve nuclear fuel safety during normal operation, operational transients and possible accident scenarios. This review introduces the latest results in the development of protective coatings for ATF claddings based on Zr alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 162 publications
0
20
0
Order By: Relevance
“…Thus, a barrier sublayer (e.g., Mo, Ta, etc.) should be additionally applied for prevention of Cr-Zr interdiffusion at temperatures higher 1300 • C [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a barrier sublayer (e.g., Mo, Ta, etc.) should be additionally applied for prevention of Cr-Zr interdiffusion at temperatures higher 1300 • C [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…During these early studies, metallic chromium coatings have shown an encouraging behavior with excellent corrosion resistance in nominal conditions, and a significant enhancement of the HT steam oxidation behavior in accidental conditions, when compared with the reference uncoated zirconium based cladding materials [11]. More recently, the studies have confirmed the good behavior of Cr coatings in steam environment at HT, up to at least 1300 • C [19][20][21][22].…”
Section: Introductionmentioning
confidence: 90%
“…CrN coatings demonstrate barrier properties at temperatures above 1350 • C, but only for thick interlayers. It is known that decomposition of CrN with formation of zirconium nitride, despite the barrier properties of ceramic coatings which are advantageous, are brittle, and small changes in temperature can lead to the formation of micro cracks and coating failures [20]. Musil proposed multilayers to prevent cracking CrN/Cr (250/250 nm) coatings against Cr-Zr inter-diffusion during heating up to 1400 • C [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid such a scenario, the oxidation resistance of the nuclear fuel claddings can be improved through the concepts of Enhanced Accident Tolerant Fuel (EATF) [ 1 ]. Among the different evolutive (i.e., short-term) EATF concepts studied so far, Cr-coated Zr-based claddings appear to be one of the most promising [ 2 , 3 , 4 , 5 ]. In doing so, metallic chromium-based coatings are deposited on zirconium cladding tubes using different processes.…”
Section: Introductionmentioning
confidence: 99%